Biodegradable radiopaque iodinated poly(ester urethane)s containing poly(ε‐caprolactone) blocks: Synthesis, characterization, and biocompatibility. Issue 4 (14th June 2013) - Sang, Lin; Wei, Zhiyong; Liu, Keliang; Wang, Xinhui; Song, Kedong; Wang, Hong; Qi, Min
Abstract: Biodegradable radiopaque iodinated poly(ester‐urethane) (I‐PU), consisting of poly(ε‐caprolactone) (PCL) diol and iodinated bisphenol A (IBPA), has been successfully synthesized via a coupling reaction of PCL‐diisocyanate and IBPA with varying compositions. The IBPA with four iodine atoms per molecule was applied as a chain extender to endow the I‐PUs with intrinsic X‐ray visibility. The chemical structure and molecular weights of I‐PUs were characterized by Fourier transform infrared spectroscopy (FT‐IR), proton‐nuclear magnetic resonance, and gel permeation chromatography (GPC). The effects of IBPA on the physical properties of I‐PUs were systematically studied by means of differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), and wide‐angle X‐ray diffraction (WAXD). The DSC results showed that the crystallization of PCL segments in I‐PUs was restrained with increasing amount of IBPA, which was also confirmed by WAXD. In the X‐radiography analysis, all the synthesized I‐PUs exhibited high radiopacity compared with an aluminum wedge of equivalent thickness. Enzymatic degradation tests showed that the incorporation of IBPA prolonged the degradation of I‐PUs and distinct mass loss and degradation happened in the third month. Basic cytocompatibility conducted using rat adipose‐derived cells proved that all the I‐PUs and their biodegradation products were nontoxic. The radiopaque I‐PUs is expected to possess a significant advantage over the traditional polymer counterparts in some related biomedical fields. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 1121–1130, 2014.